Operational risk management : a practical approach to intelligent data analysis - Kenett, Ron; Raanan, Yossi (Statistics in practice., 2010)
The book will introduce modern Operational Risk (OpR) Management and illustrates the various sources of OpR assessment and OpR mitigation. This book discusses how various data sources can be integrated and analyzed and how OpR is synergetic to other risk management activities such as Financial Risk Management and Internationalization. The topics will include state of the art technology such as semantic analysis, ontology engineering, data mining and statistical analysis.